Business success among visible and non-visible ethnic entrepreneurs: a look at the effects of unemployment, co-ethnic involvement and human capital. (1st April 2010) - Kariv, Dafna; Menzies, Teresa V.; Brenner, Gabrielle A.
This study examines the relationship between the success of businesses owned by ethnic minority immigrants in Canada and measures of their prior employment status in their homelands, their co-ethnic involvement in Canada and their educational level. Our findings show that while they were mainly unemployed prior to immigration, no significant differences in educational levels were found between groups of visible and non-visible, ethnic minority immigrants. Opposite interaction effects emerged, however, on the success of businesses owned by the visible and the non-visible ethnic groups: being more co-ethnically involved and possessing higher levels of education positively affected the success of businesses owned by non-visible ethnic groups but negatively affected the success of the visible ethnic groups. Building on concepts from Waldinger et al.'s interactive model and 'refugee'/'entrepreneurial' effects (Thurik et al., 2008), we propose an alternative view of the differences by which non-visible minority ethnic groups represent the 'entrepreneurial' effect.